Video Analisis untuk Kemampuan Menganalisis dan Memecahkan Masalah Materi Kinematika pada Calon Guru Fisika - Thoha Firdaus; A R Sinensis (Universitas PGRI Semarang, 2017)
There has been a study that demonstrates the ability to analyze and solve the problem of kinematics material in prospective physics teachers. This research uses the qualitative method. There are three techniques of data collection namely; questionnaires from students, interviews from faculty, and observation of campus environmental conditions. The results of this study produce gaps, and it can be concluded that the need for improvement and improvement of the learning model. Learning using the Video analysis program can solve the problem